HUBUNGAN POLA ASUH IBU BEKERJA DENGAN PERKEMBANGAN ANAK USIA PRASEKOLAH DI DESA PATUMBAK II TAHUN 2022 - Yeni Friska Sinulingga, Selvia Yolanda Dalimunthe, Endang Sihaloho, Mery Krista Simamora, Rida Rumondang Lubis (JURNAL PIONIR, 2022)
ABSTRACT The growth and development of children is the influenced by the pattern of parenting and the love of a mother. However, in the current era,the mothers also help the family's economic needs,for preferring to work even though they already have children. In general, parenting is defined as the attitude of parents, especially a mother in interacting with their children or the way a mother guides and educates and disciplines children. The Mothers who work most of the time their mothers spend working, so that the intensity of meeting between mothers and children is reduced. The Objective: to determine the relationship between parenting patterns of the mothers working and the social development of preschool-aged children. Methods: of the study uses a quantitative descriptive research design with a correlational descriptive approach. Sectional the sampling technique with purposive sampling based on inclusion and exclusion criteria obtained as many as 86 respondents. The instrument in the form of a questionnaire. The statistical test used in the study is the Chi-Square test. Results: The results of statistical tests using the Chi-Square Test obtained pValue = 0.003. If pValue < (0.05) it means that there is a relationship between the parenting pattern of mothers working and the social development of age children preschool in Patumbak II Village. So the statistical test results can be interpreted Ho is rejected and Ha is accepted. Conclusion: of the study with the parenting pattern of mothers working , it is hoped that children will get attention and affection from mothers, mothers learn more and pay more attention to the importance of social development for aged preschool children so that they can give full attention so that children have a high social spirit, are smart, healthy, and creative. . Keywords: Parenting Mothers working , Children's Social Development, Children preschool.         ABSTRAK Pertumbuhan dan perkembangan anak dipengaruhi oleh pola asuh ibu dan kasih sayang seorang ibu. Namun keadaan di era sekarang ibu juga membantu kebutuhan ekonomi keluarga lebih memilih bekerja walaupun sudah memiliki anak. Pola asuh ibu secara umum pola asuh didefinisikan sikap orang tua terutama seorang ibu dalam berinteraksi dengan anak-anaknya atau cara seorang ibu dalam membimbing dan mendidik serta mendisiplinkan anak. Ibu yang bekerja sebagian besar waktu ibu habis untuk bekerja, sehingga intensitas pertemuan ibu dan anak berkurang.Tujuan : untuk mengetahui hubungan pola asuh ibu bekerja dengan perkembangan sosial anak usia prasekolah.Metode : penelitian ini menggunakan desain penelitian kuantitatif pendekatan deskritif korelasional dan bersifat Cross sectional. teknik pengambilan sampel dengan purposive sampling berdasarkan kriteria inklusi dan eklusi didapatkan sebanyak 86 responden. Instrument berupa kuesioner. Uji statistik yang digunakan dalam penelitian ini adalah uji Chi-Square. Hasil : Hasil uji statistik dengan menggunakan Uji Chi-Square didapatkan nilai pValue = 0,003. Apabila pValue < α (0,05) memiliki arti ada hubungan antara pola asuh ibu bekerja dengan perkembangan sosial anak usia prasekolah di Desa Patumbak II.Sehingga hasil uji statistik dapat diartikan Ho ditolak dan Ha diterima. Kesimpulan : dengan adanya pola asuh ibu yang bekerja diharapkan anak mendapatkan perhatian dan kasih sayang dari ibu, ibu lebih mempelajari dan memperhatikan tentang pentingnya perkembangan sosial anak usia prasekolah agar dapat memberikan perhatian penuh sehingga anak memiliki jiwa sosial yang tinggi, cerdas, sehat, serta kreatif. Kata kunci : Pola Asuh ibu bekerja, perkembangan sosial anak, Anak Prasekolah